Implementation of Digital-Based Approaches in Early Childhood Education Supervision Amidst the COVID-19 Pandemic - Onny Fitriana Sitorus; Trisni Handayani; Sri Astuti (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
In the context of early childhood education, education plays a crucial role in shaping a child’s development. The COVID-19 pandemic has transformed the education landscape entirely, including early childhood education. School principals and early childhood educators have faced challenges in providing effective supervision, guidance, and evaluation in digital-based learning environments. This research aims to analyze the implementation of digital-based approaches in early childhood education supervision during the COVID-19 pandemic. Employing a survey method with a mixed-method approach, the results indicate that digital-based supervision in early childhood education exhibits limited effectiveness due to educators' lack of digital literacy, institutional unpreparedness, and suboptimal communication channels. Emphasizing digital literacy training, ensuring digital infrastructure, establishing continuous communication, and adopting user-friendly applications are crucial to enhancing educator competencies and enriching children learning experience.